2020
DOI: 10.1155/2020/1310947
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Visual Field and Balance Function Alterations in Patients Who Underwent Dermatochalasis Surgery

Abstract: Purpose. To compare perioperative visual field (VF), balance functions (BF), and changes in the other ocular parameters in patients undergoing upper eyelid dermatochalasis (DC) surgery. Methods. One hundred and fifty-eight eyes of 79 patients who underwent DC surgery were included in the study. The VF, BF, intraocular pressure (IOP), pachymetry (PM), macular, and optic nerve measurements were recorded. Measurements were repeated at postoperative month 1. The preoperative and postoperative ocular measurements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Moreover, some studies have suggested that CCT can be associated with a higher risk of developing glaucoma, even though the role CCT has on its progression and severity in patients with established glaucoma is still uncertain. [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies have suggested that CCT can be associated with a higher risk of developing glaucoma, even though the role CCT has on its progression and severity in patients with established glaucoma is still uncertain. [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%